Addition of camrelizumab to docetaxel, cisplatin, and radiation therapy in patients with locally advanced esophageal squamous cell carcinoma: a phase 1b study. (1st January 2021) - Zhang, Wencheng; Yan, Cihui; Zhang, Tian; Chen, Xi; Dong, Jie; Zhao, Jingjing; Han, Dong; Wang, Jun; Zhao, Gang; Cao, Fuliang; Zhou, Dejun; Jiang, Hongjing; et al.
ABSTRACT: Patients with locally advanced esophageal squamous cell carcinoma (ESCC) show poor survival after concurrent chemoradiotherapy. This study investigated the safety and feasibility of combining concurrent chemoradiotherapy with the anti-PD-1 antibody camrelizumab as first-line treatment for these patients. In this phase 1b study (ClinicalTrials.gov NCT03671265), patients received concurrent chemotherapy (cisplatin [25 mg/m 2 ] plus docetaxel [25 mg/m 2 ] for 4 weeks) and radiotherapy (2.0 Gy/fraction, total 60 Gy) with camrelizumab (200 mg every 2 weeks for 32 weeks). Primary endpoints were safety and tolerability, and health-related quality of life. Secondary endpoints were radiological and pathological response rates, overall survival (OS), and progression-free survival (PFS). Candidate biomarkers in tumor and peripheral blood were monitored at baseline and after 40 Gy radiation. Twenty patients were enrolled. The most common treatment-related grade 3 adverse events included radiation esophagitis (20%) and esophageal fistula (10%). Serious treatment-related adverse events occurred in eight (40%) patients. No treatment-related deaths were reported. Health-related quality of life did not deteriorate. Thirteen (65%) patients had an objective response after 40 Gy radiation. At a median follow-up of 23.7 months (95% CI 21.9–24.5), OS and PFS time ranged from 8.2–28.5 and 4.0–28.5 months, respectively. The 12-month and 24-month OS rate was 85.0% and 69.6%; PFS rate was 80.0% and 65.0%. Tumor PD-L1 expression and CD11c + dendritic cells and peripheral-blood IL-27, IL-15, Eotaxin-3, and IL-22 were associated with OS. First-line concurrent chemoradiotherapy plus camrelizumab had a manageable safety profile and promising antitumour efficacy for ESCC, and deserves further study.